Design of an elderly assistant robot platform - Yang, Jian (2017)
This final year project focus on designing a prototype of the elderly assistant robot platform. We will equip an existing research robot Pioneer3-AT with a Home Monitoring System and an indoor Navigation System. The Home Monitoring System is carried out with the help of Raspberry Pi3 mounted with several sensors and a camera. Thus, caregivers can check the home situation and environment indexes at any time anywhere through mobile devices to ensure the elderly’s safety. The indoor Navigation System is implemented by utilizing several ROS packages with customized settings and modifications. And then it can enable the robot to move freely with obstacle avoidance and path planning ability.